Colour sensor / Munadhil Hassan and Wan Mohd Zabidi Wan Muda - Hassan, Munadhil; Wan Muda, Wan Mohd Zabidi (2001)
Colour sensor is a simple circuit which is use to sense light colour of the object. This circuit used a simple electronic devices such as Integrated Circuit, Light sensor (LDR) and L F D. The function of the devices used m the circuit will be explain detailed in this project report. This circuit need to put any coloured light in front of the gadget. The gadget will detect the light colour that fall on the gadget and this circuit will determine that colour. One of the LED will be on. This circuit will detected eight colour (red. green, blue, magenta, cyan, yellow, black and white). If the primary colour that determine, only one of the LDR will triggered and the other two LDR untriggered, therefore the triggered LDR will become logic 1 to indicate which colour it is. When secondary coloured that determine, two of the LDR will get triggered and the gate out put corresponding to these will become logic one and indicate which colour it is.